2016
DOI: 10.1016/s0140-6736(16)30370-1
|View full text |Cite|
|
Sign up to set email alerts
|

Does physical activity attenuate, or even eliminate, the detrimental association of sitting time with mortality? A harmonised meta-analysis of data from more than 1 million men and women

Abstract: Lee, I. (2016). Does physical activity attenuate, or even eliminate, the detrimental association of sitting time with mortality? A harmonised meta-analysis of data from more than 1 million men and women. The Lancet, 388, s. 1302Lancet, 388, s. -1310 Dette er siste tekst-versjon av artikkelen, og den kan inneholde små forskjeller fra forlagets pdf-versjon. Forlagets pdf-versjon finner du på www.sciencedirect.com: http://doi.org/10.1016/S0140-6736 (16) MethodsWe included data from 16 studies, of which 14 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

68
1,684
11
94

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,100 publications
(1,857 citation statements)
references
References 41 publications
68
1,684
11
94
Order By: Relevance
“…Recent epidemiological evidence, including a harmonised meta-analysis of 16 prospective studies with over 1 million individuals (2-18 years follow-up) [1] probably confirm what the Diabetologia readership already suspected-too much sitting and too little physical activity are bad news. Indeed, these studies indicate that low levels of physical activity and large volumes of sedentary time (sitting) are jointly associated with increased cardiometabolic morbidity and mortality in a dose-dependent manner [1][2][3][4][5][6][7]. However, for many of those with type 2 diabetes, the more pertinent question continues to linger: what are the most effective countermeasures?…”
Section: Cgm Continuous Glucose Monitoringmentioning
confidence: 82%
“…Recent epidemiological evidence, including a harmonised meta-analysis of 16 prospective studies with over 1 million individuals (2-18 years follow-up) [1] probably confirm what the Diabetologia readership already suspected-too much sitting and too little physical activity are bad news. Indeed, these studies indicate that low levels of physical activity and large volumes of sedentary time (sitting) are jointly associated with increased cardiometabolic morbidity and mortality in a dose-dependent manner [1][2][3][4][5][6][7]. However, for many of those with type 2 diabetes, the more pertinent question continues to linger: what are the most effective countermeasures?…”
Section: Cgm Continuous Glucose Monitoringmentioning
confidence: 82%
“…Especialmente, nessa área de pesquisa, temos pouco mais de 15 anos de evidências, algo recente quando comparado ao tempo, volume e qualidade de evidências que colocaram a atividade física na agenda da saúde pública 4 . Grande parte dos estudos que levantaram a hipótese do comportamento sedentário como um fator de risco, são provenientes de investigações conduzidas em países de renda alta e que investigaram o tempo de televisão como um marcador do comportamento sedentário [2][3]5 . Os estudos que investigaram as conse-quências para a saúde do comportamento sedentário e mediram o tempo de televisão como um indicador de comportamento sedentário, de uma forma geral, encontram medidas de efeito das associações de maior magnitude quando comparados aos estudos que mediram o tempo sentado.…”
Section: Oiunclassified
“…Em um dos principais estudos até o momento dessa temática, Ekelund e colegas 5 analisaram a associação entre tempo sentado, tempo de televisão e risco de mortalidade por todas as causas em mais de um milhão de adultos. Os autores mostraram que, apesar do tempo sentado estar sozinho associado ao maio risco de mortalidade, quando a prática de atividade física foi considerada, houve uma atenuação considerável do risco de mortalidade entre os grupos mais ativos.…”
Section: Oiunclassified
See 1 more Smart Citation
“…A notable study showed that increased SB was associated with increased mortality rate, independent of PA [13]. Furthermore, a recent meta-analysis showed that SB was associated with a lower mortality rate in people with high levels of PA [hazard ratio ( [14], and interventions need to focus on reducing SB, not just increasing PA.…”
Section: Physical Activity Correlate With General Health Statusmentioning
confidence: 99%